Faktor-Faktor yang Mempengaruhi Kejadian Komplikasi Diabetes Melitus di Wilayah Kerja Puskesmas Ingin Jaya Kecamatan Ingin Jaya Kabupaten Aceh Besar - Ema Fadila Liunsanda; Tahara Dilla Santi; Dharina Baharuddin (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion or function. If left uncontrolled, this disease can lead to serious complications affecting vital organs. According to the 2023 Indonesian Diabetes Association (SKI), the prevalence of diabetes in Indonesia reached 1.7%, and in Aceh it was 1.6%. Aceh Besar Regency recorded 8,517 cases, with Ingin Jaya District ranking second with 785 cases. Widespread unhealthy behaviors increase the risk of complications. This study aims to identify factors influencing the incidence of diabetes mellitus complications, including income, family support, knowledge, attitudes, diet, physical activity, foot care, medication adherence, and blood sugar monitoring. The study used a quantitative approach with a case-control design. The population consisted of 39 individuals, with a total sampling technique, resulting in 78 respondents. The study was conducted from July 6–14, 2025, using a standardized questionnaire. Data analysis was conducted using univariate, bivariate, and multivariate methods using the chi-square test and binary logistic regression. The study results showed that physical activity (p=0.003; OR=10.360) and blood sugar monitoring (p=0.036; OR=9.806) influenced diabetes complications. Multivariate analysis confirmed these findings, while other variables showed no significant effect. It is recommended that health agencies utilize these results to strengthen health promotion, routine screening, risk factor monitoring, and improve public education on diabetes mellitus prevention and management.